PENGARUH BUAH KURMA TERHADAP KEMAJUAN PERSALINAN (Politeknik Kesehatan Kemenkes Bandung, 2022)
Labor is a physiological process that requires stamina and excellent body condition because the body's metabolism increases due to the body's muscle activities and anxiety. The body's muscle activities when the mother is ladies need optimal energy. One of the nutrients that can be consumed is dates, research shows date fruit (Dactilifera Phoenix) has a good nutritional content for the body, rich in carbohydrates, vitamins and other minerals. The purpose of this journal study is to find out the effect of giving date fruit on the progress of labor. E-Data based search method with Pubmed data source and Garuda Portal with vulnerable time 2016-2021 using keywords Date fruit, phoenix dactylifera Linn, Kurma, Labor progress, Delivery with boolean operator